2009
DOI: 10.1021/bi900478b
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Binding Activity of the Vancomycin Resistance Associated Regulator Protein VraR and the Role of Phosphorylation in Transcriptional Regulation of the vraSR Operon

Abstract: In Staphylococcus aureus the VraSR two-component system acts as a sentinel that can rapidly sense cell wall peptidoglycan damage and coordinate a response to enhance the resistance phenotype. VraR is a transcription factor and its cognate kinase, VraS, modulates the DNA-binding activity of VraR by regulating its phosphorylation state and hence its dimerization state. Here we provide the first report on the VraR transcriptional activity by investigating the interaction with the vraSR operon control region. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 35 publications
5
46
0
Order By: Relevance
“…Domain rearrangements in inactive and active VraR provide an explanation for the greater affinity of phosphorylated VraR for its target DNA sequences relative to the unphosphorylated protein (9). The DNA-binding domain consists of four α helices (Leu148 to Gln209) with a classical helix-turn-helix (HTH) DNA-binding motif that defines members of the NarL/FixJ response regulator subfamily, as previously reported for the NMR structure of the isolated domain (25).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Domain rearrangements in inactive and active VraR provide an explanation for the greater affinity of phosphorylated VraR for its target DNA sequences relative to the unphosphorylated protein (9). The DNA-binding domain consists of four α helices (Leu148 to Gln209) with a classical helix-turn-helix (HTH) DNA-binding motif that defines members of the NarL/FixJ response regulator subfamily, as previously reported for the NMR structure of the isolated domain (25).…”
Section: Resultsmentioning
confidence: 66%
“…A fluorescence anisotropy assay was developed to measure the affinity of VraR and VraR M13D with the putative R1 VraR binding site DNA (9). See SI Materials and Methods for experimental conditions and procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA sequence derived from the vraSR operon control region, which encompasses nucleotides Ϫ121 to ϩ26, was amplified by PCR using the genomic DNA of S. aureus RN4220 as a template and was cloned in the blunt-end vector pSTBlue-1 as previously described (2). The resulting plasmid was named pSTblue-1:: P vraSR .…”
Section: Kmno 4 Footprinting Assaymentioning
confidence: 99%
“…1), referred to as the R1, R2, and R3 sites (2). VraR binding sites centered at positions Ϫ60 and Ϫ35 were analyzed independently, and in vitro studies showed binding of VraR to R1 was not affected by phosphorylation of VraR, while unphosphorylated VraR did not bind to R2.…”
mentioning
confidence: 99%